Quality of Life of Palestinian Patients on Hemodialysis: Cross-Sectional Observational Study - Hani H. Naseef; Nadin Haj Ali; Arin Arafat; Sawsan Khraishi; Abdallah Damin AbuKhalil; Ni’meh Al-Shami; Hosniyeh Ladadweh; Mohammad Alsheikh; Abdullah K. Rabba; Imad T. Asmar; Yousef Sahoury (The Scientific World Journal)
Background. Hemodialysis is life-saving and life-altering, affecting patients’ quality of life. The management of dialysis patients often focuses on renal replacement therapy to improve clinical outcomes and remove excess fluid; however, the patient’s quality of life is often not factored in. Objective. This study aimed to explore the factors affecting the quality of life of patients on dialysis in Palestine using the Kidney Disease Quality of Life (KDQOL-SFTM) questionnaire. Methods. A multicenter cross-sectional observational study was conducted at multiple dialysis centers in Palestine, including 271 participants receiving renal replacement therapy. Demographics, socioeconomic, and disease status data were collected. The Arabic version of KDQOL-SFTM was used to assess dialysis patient quality of life. Statistical analysis was performed using SPSS to find correlations among patient factors and the questionnaire’s three main domains, the kidney disease component summaries (KDCS), mental component summaries (MCS), and physical component summaries (PCS). Results. Mean KDCS, MCS, and PCS scores were 59.86, 47.10, and 41.15, respectively. KDC scores were lower among participants aged 40 years or older, with lower incomes, and with diabetes. PCS and MCS scores were lower among patients aged >40, less educated, and lower-income participants. There was a positive correlation between MCS and KDCS (r = 0.634, P-value <0.001), PCS and KDCS (r = 0.569, P-value <0.001), as well as MCS and PCS (r = 0.680, P-value <0.001). Conclusion. In this study, the KDQOL-SFTM questionnaire revealed lower PCS scores among hemodialysis patients in Palestine. Furthermore, the three domains of the questionnaire were adversely affected by patient income and education status. In addition, physical role, work status, and emotional role showed the lowest scores among the three main domains. Therefore, continuous assessment of patients’ quality of life during their journey of hemodialysis using the KDQOL-SFTM along with the clinical assessment will allow the healthcare professionals to provide interventions to optimize their care.